The impact of the physical environment on student achievement of Public Elementary School students in Koronadal City - Saquilabon, Hannah Liza A.; Cartajenas, Ken Alexis S. (2014)
Primary education is where children were molded to become the individuals that they would be in the future and the first step to achieve their dreams. However, the state of the public elementary schools in the country is not very ideal for learning as most of the classrooms were poorly built due to budget constraints from the government. This study wanted to examine if the quality of the school environment of public elementary school students in the City of Koronadal is correlated with their academic performance. 31 public elementary schools were included in the study. The National Achievement Test mean score of each school from the last three years were taken from the Division office of DepEd Koronadal for the measure of student achievement of each school. For the measure of the condition of each school, the CAPE instrument develop by Cash 1993 was used. The variables were used under aesthetics and building components. Correlation between the two variables was analyzed by using SPSS; Pearson?s r was used to determine if two variables were correlated. Results showed that there was a positive correlation between the two variables. Wall painting cycles, roof leaks, school age, noise and classroom furniture came out to be the best factors that are related with a student?s academic performance
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2014